Participatory human development in post-apartheid South Africa: a discussion of the 2006/7 Tantyi Youth Empowerment Project - Kulundu, Injairu M (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
This thesis relates the work of a non-governmental organisation, The Spirals Trust, to discussions on human and participatory development. The focus of the study is one of The Spirals Trust's projects, the 2006/7 Tantyi Youth Empowerment Project, which is discussed in relation to theoretical material on human development and participatory development. Collectively these perspectives are defined in this thesis as 'participatory human development'. The 2006/7 Tantyi Youth Empowerment Project illustrates some of the challenges that face the practice of participatory human development. Workshops and focus group interviews were conducted with participants who were part of the 2006/7 Tantyi Youth Empowerment Project in order to draw out their experiences of the project. Questions were created from themes that emerged from the participants' discussion of their experiences and these questions were then posed to members of staff of The Spirals Trust. The experiences of both the participants and the staff members are discussed in order to explore issues that emerge in the practice of participatory human development in the 2006/7 Tantyi Youth Empowerment Project. The results highlight the challenges of putting into action the tenets of participatory human development. Feedback showed that a focus on personal development can help cultivate the ethic of participation. The effort that this entailed on the part of facilitators is discussed. The importance of exposing and continually working with power dynamics that may emerge in projects of this nature is revealed and the eroding influence of bureaucratic compliance in projects like this one is explored. The study also suggests that there is a need to promote development initiatives that challenge the political status quo rather than just finding ways to incorporate the marginalised more effectively into current systems. New questions that the research poses to the practice of participatory human development are considered in conjunction with suggestions for further research.
Keywords: Spirals Trust (South Africa)|Community development -- South Africa -- Citizen participation|Economic development projects -- South Africa -- Citizen participation|Youth in development -- South Africa|Non-governmental organizations -- South Africa|Post-apartheid era -- South Africa|South Africa -- Politics and government -- 1994-